2005
DOI: 10.1016/j.icesjms.2005.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of Merluccius merluccius along the Iberian Peninsula coast

Abstract: Prespawning hake caught in eight locations around the Iberian Peninsula were genetically analysed. The distribution of variation at five microsatellite loci suggests that the species follows a population model of isolation by distance in this geographical area. Three different areas can be identified: the Mediterranean Sea, the Portuguese coast, and the Cantabric Sea. The lack of differentiation between samples caught in the VIIIa,b,d and in the VIIIc ICES Areas suggests that, based on genetic information, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…In the light of the present results on the dynamics of Northern and Southern Stocks of hake in recent years it seems that the European hake probably comprises a single population in North Atlantic but has different sub-populations. This hypothesis is supported by genetic and parasitological studies (Lo Brutto et al, 2004;Mattiucci et al, 2004;Castillo et al, 2005) …”
Section: Changes In Maturity Ogives In Response To Environmental Flucmentioning
confidence: 66%
See 1 more Smart Citation
“…In the light of the present results on the dynamics of Northern and Southern Stocks of hake in recent years it seems that the European hake probably comprises a single population in North Atlantic but has different sub-populations. This hypothesis is supported by genetic and parasitological studies (Lo Brutto et al, 2004;Mattiucci et al, 2004;Castillo et al, 2005) …”
Section: Changes In Maturity Ogives In Response To Environmental Flucmentioning
confidence: 66%
“…However, some controversy exists about the stock structure of European hake in the Atlantic. Some authors consider that there is no separation between traditional Northern and Southern stock because of intense gene flow related to the current systems of this area (Balado et al, 2003) Recent studies based on genetic and biological parameters and incidence of identified parasites used as tags for stock identification suggest that only one stock is really differentiated in the North-east Atlantic; although probably two sub-populations exist and are separated by the Cape Breton Canyon (Lo Brutto et al, 2004;Mattiucci et al, 2004;Castillo et al, 2005). These results are relevant for management purpose and the boundary between these stocks should be reconsidered based on biological evidence.…”
Section: Maturity Ogivesmentioning
confidence: 99%
“…Thus, the BoB delimits the southern extent area of the Northern Stock, while the Galician Shelf (GS) defines the northern limits of the Southern stock. However, it seems that there is neither geographical nor genetic evidence to support the location of a barrier between the stocks (Mattiucci et al, 2004;Castillo et al, 2005). In fact, several previous studies on the ecotypes of European hake species do not support the existence of a boundary between Northern and Southern hake stocks (Roldán et al, 1998(Roldán et al, , 1999Lundy et al, 2000;Pineiro et al, 2007) and more conclusive studies based on biological evidence are required to demonstrate the separation of populations within the present stocks range (Lundy et al, 1999).…”
Section: Introductionmentioning
confidence: 92%
“…Carvalho and Hauser, 1994;Berkeley et al, 2004). Genetic differences between regions have been described for many species, including mackerel (Nesbø et al, 2000), Atlantic cod (Nielsen et al, 2001), turbot (Nielsen et al, 2004), European hake (Lundy et al, 1999;Castillo et al, 2004Castillo et al, , 2005, Austral hake (Machado-Schiaffino et al, 2009) and others. These studies are generally based on DNA-based markers.…”
Section: Introductionmentioning
confidence: 99%